La satisfacción laboral y su relación con el desempeño laboral del sector lácteo en el cantón Latacunga - Escobar Teneda, Alex Marcelo (2023)
Nowadays, due to the strong changes that the labor sector suffered after a global pandemic and the changes or challenges of the market that demand more skills and knowledge, companies need to implement exchanges to face the challenges that arise, since from this depends on the satisfaction and performance of your workforce. Companies in the dairy sector in the Latacunga canton, Cotopaxi province are affected by a crisis of an economic, social, cultural nature, among others. For this reason, this research sought to determine the relationship between Satisfaction and Job Performance through the implementation of measurement instruments that helped us collect information to establish the relationship between job satisfaction that their workers have and how this influences their job performance.